Extractives, holocellulose, α-cellulose, lignin, and ash contents in 3 year-old bamboo culms gigantochloa brang, G. Levis, G. Scortechinii and G. Wrayi - Razak Wahab; Mohd Tamizi Mustafa; Aminuddin Mohamed; Hashim W. Samsi; Mohd Sukhairi Mat Rasat (RJPBCS, 2013)
The chemical contents in cultivated 3 year-old bamboo culms of Gigantochloa brang, G. levis, G. scortechinii and G. wrayi were studied. Different composition were exhibited in the extractives, holocellulose, α-cellulose, lignin, and ash contents between the four (4) bamboo species, location in the culms and position at the nodes and internodes. The extractive content in four species ranged from 8.30 to 9.23%. The extractive content of G.brang, G.levis, G.scortechinii and G.wrayi were 8.30%, 9:23%, 8:00% and 8.62% respectively. The holocellulose content for G. levis were 85.08%, G. wrayi 84.53%, G. brang 79.94% and G. scortechinii 74.62%. The holocellulose content for the cultivated bamboo genus Gigantochloa were 74% to 85%. The α-cellulose is the chemical constituents in the holocellulose. The highest was G.brang (51.58%) followed by G. scortechinii (46.87%), G.wrayi (37.66%) and G. levis (33.80%). The lignin content ranged between 24.84 to 32.65%.The highest were obtained in G. scortechinii (32.55%), G. wrayi (30.04%%), G. levis (26.50%) and lowest in G. brang (24.83%). The ash content in four species of Gigantochloa bamboo ranged between 0.88 to 2.86%. The ash content is the highest in G. scortechinii (2.83%) follow by G. levis (1.29%), G. brang (1.25%) and the lowest in G.wrayi (0.88%).